PWE-147 Nurse Led Day Case Paracentesis. (9th June 2014) - Dwyer, L; Tobin, L
Abstract : Introduction: Refractory ascites is a debilitating condition. Prior to the implementation of nurse led day case paracentesis all patients were admitted into the hospital for an inpatient stay of between 3 and 5 days. An audit of inpatient paracentesis was carried out to assess the quality and efficiency of inpatient paracentesis. From this the service was developed to improve the overall quality of the patient experience and reduce inpatient admissions for paracentesis. Disease aetiology includes alcoholic liver disease, viral disease, autoimmune disease and advanced malignancy. Methods: The hepatologist CNS was trained by the consultant hepatologist to perform paracentesis. All patients requiring paracentesis are referred directly to the CNS from GP's, out patient clinics and the accident and emergency department. Patients are assessed in a pre procedure clinic by the CNS. A clinical examination is performed, bloods are checked and if necessary corrected accordingly to facilitate day case paracentesis. To date, the CNS has performed over 200 day case paracentesis procedures and complication rates remain below the national average. Results: Data collected from a patient feedback exercise was extremely positive in all aspects of the nurse led day case paracentesis service. An audit of the service demonstrated no difference in overall outcomes when the CNS performed the paracentesis in comparison to the medical registrar. There has been a significant reduction in hospital bed days required for paracentesis. Conclusion: Nurse led day case paracentesis is a safe, effective and economic alternative to costly inpatient hospital admissions. It has proven to be both beneficial to the service user and the NHS trust. Patients benefit from a key worker who specialises in the management of refractory ascites who can provide management and out patient intervention to avoid the potential compliactions of large volume refractiory ascites and unnecessary hospital admissions. Disclosure of Interest: None Declared.